Enterovirus infection in children attending two outpatient clinics in Zhejiang province, China. Issue 9 (12th February 2014) - Cai, Jian; Lv, Huakun; Lin, Junfen; Chen, Zhiping; Fang, Chunfu; Han, Jiankang
<x xml:space="preserve">Abstract</x> Enteroviruses are responsible for hand, foot, and mouth disease, and have caused many deaths in China during recent years. But the natural history of enterovirus infection in children, especially asymptomatic children, is not yet clear. From April 2011 to May 2012, 505 stool and throat swab samples of children attending outpatients clinics in two hospitals were collected weekly to test for Enterovirus 71, Coxsackievirus A16, and other enterovirus nucleic acids by real‐time RT‐PCR. Two hundred sixty‐four patients were enterovirus positive, the positive rate was 52.3%, 27.5% (22/80) in children without a rash and 56.9% (242/425) in children with a rash. Coxsackievirus A16 positive rate of male (24%, 61/254) was higher than that of female (15.2%, 26/171) (χ2 = 4.87, P = 0.027). The highest positive rate of enterovirus infection was 63.5% in the 2‐year‐old age group. Comparing children with and without a rash, within the same age groups, no statistical difference was found (P > 0.05). The seasonal distribution of Enterovirus 71 had only one peak in May, but Coxsackievirus A16 had two peaks in April and October. In patients with a rash, the frequency of Enterovirus 71 was relatively high before July, and then that of Coxsackievirus A16 increased gradually. In the case of Enterovirus 71 and Coxsackievirus A16, stool specimens had a higher positive rate than throat swab specimens' (χ2 = 3.88, P = 0.05; χ2 = 15.13, P < 0.001). Enterovirus infection was more frequent in males 2–3 year‐old children, with the implicated virus varying by season. Targeted prevention and control measures should be carried out. J. Med. Virol. 86:1602–1608, 2014. © 2014 Wiley Periodicals, Inc.